Shifting from experience economy to memorable tourism experience: an overview from ecotourism - Subramaniam, Thanam; Samdin, Zaiton; Ramachandran, Sridar; Puvaneswaran, Kunasekaran (American Scientific Publishers, 2018)
This article provides an overview of the current literature on memorable tourism experiences (MTE) in the ecotourism sector. Malaysia, as a developing country, is improving its policies in the ecotourism sector to attract more international tourists and to generate national revenue. Thus, creating memorable tourism experiences among tourists was identified as an essential tool to attract new tourists and to keep existing ones as repeat visitors. Even though several studies were conducted on MTEs, there is lack of literature, especially focussing on the ecotourism sector. The literature review used the following keywords: ‘Experience Economy-Progression of Economic Value and Four Realms of Experience,’ ‘Tourism experience’ and ‘Memorable Tourism Experiences.’ The study used content analysis to examine 14 MTE articles. The findings indicated that only four MTE studies were conducted in the ecotourism sector (natural park, boating sector, wildlife and winter tourism) in the past seven years. Furthermore, the analysis highlighted that only seven key variables of MTEs (hedonism, novelty, meaningfulness, local culture, refreshment, involvement and knowledge) were frequently used in these articles, even though the originator initiated 18 variables. Therefore, the study recommends more studies be conducted by including all 18 variables and destination attributes. Additionally, new indicators, such as nature and education awareness should be added to more fully develop the Memorable Ecotourism Experiences (MEEs) conceptual model.